Nitrogen Balance in Coffee-Based Agroforestry System: An Impact of Fertilization Management - Siahaan, Adiva Zulaika Azalia; Prasetya, Budi; Nugroho, R Muhammad Yusuf Adi Pujo; Kurniawan, Syahrul (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Nitrogen (N) fertilization in coffee agroforestry system requires proper management to increase N use efficiency (NUE) and minimize N losses. This study investigated the impact of different fertilization management on N losses, N uptake, and N storage in a coffee-based agroforestry system. The study was conducted using three types of fertilizer (organic, inorganic, and mixture of organic-inorganic) with three doses (low, medium, and high), and a control treatment (no fertilization), with 3 replications. Soil leachate was collected using lysimeter at 50 cm depth (below coffee root zone) and gas emissions were collected monthly using chamber for 4 months. Soil sample at 0-20 cm depth and leaf sample were also collected. The variables included NH₄⁺ and NO₃ˉ concentration in the leachate and soil, soil N total, N uptake, N emission, N use efficiency (NUE) and partial N balance. Results showed no significant differences in N leaching or plant N uptake across treatments. However, the mixed fertilizer with high dose treatment significantly increased soil N availability while reducing N₂O emissions and improving the overall N balance. This suggests that a high dose mixed fertilizer application can enhance N utilization in coffee-based agroforestry systems, potentially improving productivity while minimizing environmental impacts. Keywords: Agroforestry, Fertilization, Nitrogen balance, Nitrogen loss, Nitrogen storage.